Computers and schools - Shears, Lawrie (Camberwell, Vic. : Australian Council for Educational Research, 1995)
Introduction. Computer use in Victorian schools. Laptops in schools. Project team's responses.
Keywords: Education; Schools; Computers; Computer-assisted instruction -- Victoria -- Case studies; Laptop computers -- Victoria -- Case studies; Education -- Victoria -- Data processing -- Case studies